Guidelines for native seed production and grassland restoration - Kiehl, Kathrin 1964-; Kirmer, Anita; Shaw, Nancy; Tischew, Sabine (Cambridge Scholars Publishing, 2014)
World-wide, the degradation and destruction of both natural and traditionally used semi-natural ecosystems is drastically increasing. Unfortunately, commercial seed mixtures, consisting of non-native species and genetically uniform cultivars, are widely used in grassland restoration, often with negative effects on biodiversity. Therefore, native species should be used in the ecological restoration of natural and semi-natural vegetation. This book compiles results from recent studies presented at a Special Session "Native seed production and use in restoration projects", which was organised during the 8th European Conference on Ecological Restoration in Ceské Budejovice, Czech Republic. The authors review the ecological and genetic aspects of seed propagation and species introduction both from a European and an American perspective, and discuss implications for the development of seed zones and for native seed production. Examples from different countries focus on native seed production in practice, and suggest different approaches for the certification of seed provenance. Best practice examples from Europe and the United States are used to indicate the advantages of using native seeds for ecological restoration of grasslands, field margins and sagebrush steppe. Finally, this volume also provides guidelines for the successful implementation of restoration projects for local authorities, landscape planners and NGOs in order to bridge gaps between research and practice